Fatty acids role on obesity induced hypothalamus inflammation: from problem to solution – a review - Salsinha, Ana Sofia (2021)
Background: Obesity has currently reached a worldwide pandemic level, playing a central role in the development of non-communicable diseases and in health care burden. The available drugs for obesity have not achieved the required level of clinical effectiveness and have been associated with severe health side effects. Recent investigations suggest that obesity is more complex as it is associated with altered brain functions. Scope and approach: In this review the hypothalamus inflammation was presented as playing a major role in obesity development and progression. The role of diet, namely western pattern diet, was presented as one of the major responsible for such inflammation focusing on saturated fatty acids role, since they bind to toll-like receptor 4 (TLR 4) triggering inflammatory processes. In contrast, the anti-inflammatory ability of polyunsaturated fatty acids was described and the potential of using conjugated fatty acids in antiobesogenic therapies specifically aiming hypothalamic inflammation was, for the first time, postulated. Key findings and conclusions: Promising hypothalamic anti-inflammatory effects of omega-3 fatty acids, mediated by G protein receptor 120 (GPR120), have been extensively described and present promising results in diet-induced obesity studies. Besides, several in vivo and in vitro studies have demonstrated beneficial effects of conjugated linoleic acid (CLA) and conjugated linolenic acid (CLNA) isomers on aspects related to immune function and inflammation, also presenting an anti-inflammatory effect. Moreover, they were successfully described to decrease peripheral obesity effects. Nevertheless, few studies have specifically addressed the effect of those isomers on obesity-induced hypothalamic inflammation and further investigations are warranted.